The Influence of Electronic Service Quality and Perceived Value on Customer Loyalty of VIDIO DOT COM in Pontianak City Through Satisfaction as an Intervening Variable - Aqmal Zulmin Layardi; Muhammad Ebuziyya Alif Ramadhan (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to analyze the influence of electronic service quality and perceived value on customer loyalty of Vidio.com in Pontianak City, with customer satisfaction as an intervening variable. The research employs a quantitative approach with an associative research design. The population of this study consists of residents of Pontianak City who have used Vidio.com services. The sample was determined to be 100 respondents using purposive sampling techniques, with criteria including a minimum age of 18 years and having used Vidio.com at least once. Data were collected using questionnaires and analyzed using SEM-PLS through SmartPLS 3 software. Evaluation of the measurement model (outer model) was conducted through convergent and discriminant validity tests, Average Variance Extracted (AVE) values, and construct reliability. Evaluation of the structural model (inner model) was performed using R-square values and testing of direct and indirect effects through bootstrapping. The results show that electronic service quality does not have a significant effect on satisfaction, while perceived value has a positive and significant effect on satisfaction. Satisfaction has a positive and significant effect on customer loyalty. Furthermore, electronic service quality and perceived value do not have a direct effect on loyalty. In mediation testing, satisfaction does not mediate the effect of electronic service quality on loyalty, but it significantly mediates the effect of perceived value on loyalty.